JavaServer faces - Bergsten, Hans (O'Reilly, 2004)
JavaServer Faces, or JSF, brings a component-based model to web application development that's similar to the model that's been used in standalone GUI applications for years. The technology builds on the experience gained from Java Servlets, JavaServer Pages, and numerous commercial and open source web application frameworks that simplify the development process. In JavaServer Faces, developers learn how to use this new framework to build real-world web applications. The book contains everything you'll need: how to construct the HTML on the front end; how to create the user interface components that connect the front end to your business objects; how to write a back-end that's JSF-friendly; and how to create the deployment descriptors that tie everything together. JavaServer Faces pays particular attention to simple tasks that are easily ignored, but crucial to any real application: working with tablular data, for example, or enabling and disabling buttons. And this book doesn't hide from the trickier issues, like creating custom components or creating renderers for different presentation layers. Whether you're experienced with JSF or a just starting out, you'll find everything you need to know about this technology in this book. Topics covered include: The JSF environment Creating and rendering components Validating input Handling user-generated events Controlling page navigation Working with tabular data Internationalization Integration between JSF and Struts Developing custom renderers and custom componentsJavaServer Faces is a complete guide to the crucial new JSF technology. If you develop web applications, JSF belongs in your toolkit, and this book belongs in your library.